Cochrane Database of Systematic Reviews 2011
DOI: 10.1002/14651858.cd003380.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and educational interventions for preventing depression in children and adolescents

Abstract: Background Depression is common in young people, has a marked negative impact and is associated with self-harm and suicide. Preventing its onset would be an important advance in public health. Objectives To determine whether psychological or educational interventions, or both, are effective in preventing the onset of depressive disorder in children and adolescents. Search methods The Cochrane Depression, Anxiety and Neurosis Review Group's trials registers (CCDANCTR) were searched at the editorial base in July… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
261
4
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(283 citation statements)
references
References 271 publications
10
261
4
8
Order By: Relevance
“…Las características del contenido de la intervención (por ejemplo, un enfoque en la formación de resolución de prob lemas o la reducción de co gniciones negativas) y su diseño (por ejemplo, el uso o no de asignación aleatoria y la evaluación mediante entrevistas estructuradas o sin ellas) era independiente de los tamaños del efecto. Merry et al (2011) 53 estudios 1. Se halló una reducción significativa del riesgo de tener un trastorno depresivo tras la intervención y en los seguimientos a los 3, 9 y 12 meses.…”
Section: Horowitz Yunclassified
“…Las características del contenido de la intervención (por ejemplo, un enfoque en la formación de resolución de prob lemas o la reducción de co gniciones negativas) y su diseño (por ejemplo, el uso o no de asignación aleatoria y la evaluación mediante entrevistas estructuradas o sin ellas) era independiente de los tamaños del efecto. Merry et al (2011) 53 estudios 1. Se halló una reducción significativa del riesgo de tener un trastorno depresivo tras la intervención y en los seguimientos a los 3, 9 y 12 meses.…”
Section: Horowitz Yunclassified
“…Positive effects on personal and social outcomes have been found for some depression prevention programs (Merry et al, 2011). Moreover, some evidence has been found that preventive interventions for depression can be effective strategies for health savings (Mihalopoulos et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent meta-analysis of Merry, Hetrick, Cox, Brudevold-Iversen & McDowell (2011), concluded that there is sufficient evidence to say that prevention programs for depression, targeted and universal, can prevent the onset of depressive disorders. For an even more recent review see .…”
Section: Introductionmentioning
confidence: 99%
“…Bij het voorkomen en verminderen van emotionele problemen bij kinderen en jeugdigen maken de meeste interventies gebruik van cognitieve gedragstherapie (Van Rooijen & Ince, 2013;Bienvenu & Ginsburg, 2007;Ginsburg, 2004;Horowitz & Garber, 2006;Meijer, Smit, Schoemaker & Cuijpers, 2006;Barrett & Turner, 2004;Merry, Hetrick, Cox, Brudevold-Iversen, Bir & McDowell, 2011;Mychailyszyn e.a., 2012). De adviezen die de JGZ geeft aan ouders en kind kunnen gestoeld worden op deze aanpak.…”
Section: Adviezen Ter Preventie Van Emotionele Problemenunclassified